#sustainablefashion – A Conceptual Framework for Sustainable Fashion Discourse on Twitter. Issue 1 (2nd January 2021) - Orminski, Jeanette; Tandoc Jr., Edson C.; Detenber, Benjamin H.
ABSTRACT: The concept of sustainability has gained in importance since the United Nations made it the main pillar for development in 1992. But while areas like climate change and energy consumption are well known, the concept of sustainable fashion is neither understood nor conceptualized very well. Most research in the field focuses on fashion consumption but has various understandings of sustainability. Through a text-based analysis of the Twitter discourse on sustainable fashion, this study developed a conceptual framework to understand perceptions of sustainable fashion that can help guide theory and practice. The findings contribute to the development of a circular model of sustainable fashion that combines production, diffusion, and consumption processes. The utility and limitations of the conceptual model are discussed.